Bioactivity of endodontic biomaterials on dental pulp stem cells through dentin - Bahar Javid; Narges Panahandeh; Hassan Torabzadeh; Hamid Nazarian; Ardavan Parhizkar; Saeed Asgary (Restorative Dentistry & Endodontics)
ObjectivesThis study investigated the indirect effect of calcium-enriched mixture (CEM) cement and mineral trioxide aggregate (MTA), as 2 calcium silicate-based hydraulic cements, on human dental pulp stem cells (hDPSCs) through different dentin thicknesses.Materials and MethodsTwo-chamber setups were designed to simulate indirect pulp capping (IPC). Human molars were sectioned to obtain 0.1-, 0.3-, and 0.5-mm-thick dentin discs, which were placed between the 2 chambers to simulate an IPC procedure. Then, MTA and CEM were applied on one side of the discs, while hDPSCs were cultured on the other side. After 2 weeks of incubation, the cells were removed, and cell proliferation, morphology, and attachment to the discs were evaluated under scanning electron microscopy (SEM). Energy-dispersive X-ray (EDXA) spectroscopy was performed for elemental analysis. Alkaline phosphatase (ALP) activity was assessed quantitatively. The data were analyzed using the Kruskal-Wallis and Mann-Whitney tests.ResultsSEM micrographs revealed elongated cells, collagen fibers, and calcified nucleations in all samples. EDXA verified that the calcified nucleations consisted of calcium phosphate. The largest calcifications were seen in the 0.1-mm-thick dentin subgroups. There was no significant difference in ALP activity across the CEM subgroups; however, ALP activity was significantly lower in the 0.1-mm-thick dentin subgroup than in the other MTA subgroups (p < 0.05).ConclusionsThe employed capping biomaterials exerted biological activity on hDPSCs, as shown by cell proliferation, morphology, and attachment and calcific precipitations, through 0.1- to 0.5-mm-thick layers of dentin. In IPC, the bioactivity of these endodontic biomaterials is probably beneficial.